Effectiveness of Legal Protection on Employees/Labours in a Fixed-Term Employment Contract in Golden Tulip Bay View Hotel & Convention-Bali - Ririh Wijayanti (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract In every company, work agreement (contract) initiates an employment relationship between employees/labours and employers. The working relationship at Golden Tulip Bay View Hotel & Convention-Bali is realized in the form of Fixed-Term Employment Contract (PKWT) which in its implementation is not in accordance with the provisions of Law Number 13 of 2003 concerning Employment because it harms employes/labours. This study analyzes the effectiveness of legal protection for employees under PKWT at Golden Tulip Bay View Hotel & Convention-Bali. This study was conducted in empirical legal research design. The results of the study show that a number of irregularities occur in the implementation of PKWT rules since they do not comply with or are even not referred to Law Number 13 of 2003 concerning Employment. The obstacles faced in the implementation of legal protection for employees/labour under PKWT at Golden Tulip Bay View Hotel & Bali Convention are Juridical and Non-Juridical barriers. Therefore, legal protection for the employees under PKWT at Golden Tulip Bay View Hotel & Convention-Bali is not sufficient. Keywords: Employees/Labours; Legal Protection; PKWT